Sistem Pendukung Berfikir Kreatif dalam Proses Perancangan Produk - Widyat Nurcahyo; M. Yusman (Jurnal Ilmiah ESAI, 2010)
Innovation has been acknowledged as the key for business success. Creativity as the core in innovation process has a strategic role. A number of creative thinking methods have been created to help people to be more creative. This thesis proposes an information system that supports creative thinking process in the idea-generation phase in the product design environment. This system is based on a few creative thinking methods such as TRIZ (Theory of Inventive Problem Solving), Tony Buzan’s Mind-Map, and Edward de Bono’s Lateral Thinking. When a problem is registered, the system will present TRIZ solutions from the contradiction matrix, related ideas that have been stored in the database, a random picture to generate left-brain/right-brain association, and a random word as a trigger for de Bono’s random input and provocative operation. Users, as a team, will discuss it in a brainstorming session, and then input the generated-ideas into the system. As the results, we hope that the idea-generation phase in the product design environment will be more productive. Finally, with the creative ideas repository, the company could maintain knowledge as its most valuable asset. Key words  :    Creative Thinking Supporting System, Product Planning, TRIZ, Lateral Thinking, Mind-Map.